THE RELATIONSHIPS OF PSYCHOLINGUISTICS IN ACQUISITION AND LANGUAGE LEARNING - Lumentut, Yuliana; Lengkoan, Fergina (English Education Department, 2021)
Through psychology we can learn about how students attitudes and behaviors in acquiring and learning languages while through linguistics we can learn about language concepts and structures At the stage of language acquisition there are four phases of language acquisition in the child 1 the level of the starting from age 0 sampai1 years 2 period of holophrase starting at the age of 1 to 2 years 3 The two word greeting period starting at 2 to 2 years 6 months 4 The starting period of grammar starting at 2 years 6 months up to 3 years and above And the four advanced stages are; 1 Sensorimotor stage birth up to age 2 3 years 2 Pre operational stage 3 to 6 or 7 years old 3 concrete operational stage aged 6 7 years to 11 or 12 years 4 Formal operational stage 12 years old to adulthood It is not important to learn anywhere while not in the classroom as long as the process of learning is directed at the mastery of the rules of the language consciously by educators as well as learners the process is called learning During the formal and informal learning process the psycholinguistic process works to acquire language knowledge through a study So this interdisciplinary can lead educators to understand the process that happens in every student who is faced with when they are trying to understand and identify the material understanding in language learning presented in the classroom < p>